2017
DOI: 10.1186/s13040-016-0122-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated transcriptional levels of aldolase A (ALDOA) associates with cell cycle-related genes in patients with NSCLC and several solid tumors

Abstract: BackgroundAldolase A (ALDOA) is one of the glycolytic enzymes primarily found in the developing embryo and adult muscle. Recently, a new role of ALDOA in several cancers has been proposed. However, the underlying mechanism remains obscure and inconsistent. In this study, we tried to investigate ALDOA-associated (AA) genes using available microarray datasets to help elucidating the role of ALDOA in cancer.ResultsIn the dataset of patients with non-small-cell lung cancer (NSCLC, E-GEOD-19188), 3448 differentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 40 publications
(44 reference statements)
1
24
0
Order By: Relevance
“…In the present study, we found that ALDOA knockdown resulted in G 1 /S blockage. Similarly, previous bioinformatics analysis results suggest a correlation between ALDOA and the cell cycle in NSCLC [ 47 ]. These results imply that ALDOA plays a role in the occurrence of NSCLC and is a potential early marker of NSCLC.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, we found that ALDOA knockdown resulted in G 1 /S blockage. Similarly, previous bioinformatics analysis results suggest a correlation between ALDOA and the cell cycle in NSCLC [ 47 ]. These results imply that ALDOA plays a role in the occurrence of NSCLC and is a potential early marker of NSCLC.…”
Section: Discussionsupporting
confidence: 69%
“…In the pancreas, it promotes tumorigenesis and progression into a highly metastatic pancreatic cancer by regulating the expression of E‐cadherin . It regulates the cell cycle in non‐small cell lung cancer and several solid tumours …”
Section: Discussionmentioning
confidence: 99%
“…ALDOA, which is a highly conserved gene among different species and a well-studied member of the aldolase family, has been reported to be upregulated in various types of tumor cells, including oral squamous cell carcinoma, osteosarcoma, hepatocellular carcinoma and lung cancer [22-26]. Du et al found that ALDOA might promote the progression of lung cancer through EMT [27].…”
Section: Discussionmentioning
confidence: 99%